RocketHA: A High Availability Design Paradigm for Distributed Log-Based Storage System - Ji, Juntao; Jin, Rongtong; Fu, Yubao; Gu, Yinyou; Tsai, Tsung-han; Lin, Qingshan (IEEE/ACM International Conference on Automated Software Engineering : [proceedings], 2023)
As a team from Alibaba Cloud, we have developed and open-sourced RocketMQ, a cloud-native "messaging, eventing, streaming" real-time data processing platform that covers cloud-edge-device collaboration scenarios. During the development of RocketMQ, we also formulated RocketHA, a log-based storage high availability design theory that provides a robust solution for distributed log storage software used in industrial applications. RocketHA comprises six fundamental components that enable automatic cluster recovery from failures such as crashes and partitions. This design paradigm has been successfully implemented in the open-source RocketMQ. Our evaluation demonstrates that RocketHA ensures high availability, fast recovery, high throughput, and data loss prevention. We hope that RocketHA will inspire and guide the development of high-availability solutions for all log-based storage systems.